THE EFFECT OF SOWING TIMES AND MINERAL FERTILIZER RATE ON SUGAR BEET GROWTH AND STONE THICKNESS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
As is known, obtaining a plentiful and high-quality harvest from any plant directly depends on its planting dates. This factor has been studied by many scientists in various plants and appropriate recommendations have been made. The weight and quality of the harvest from sugar beet also depend on its planting dates and healthy and early germination of seeds. Therefore, in the dissertation, the dynamics of sugar beet germination depending on the planting dates were studied, and calculations were carried out every three days. This article provides information on the effect of planting dates and mineral fertilizer rates on sugar beet germination and seedling thickness.